Critical Review in the application of the concept of Qath'iy and Dzanny to the Quran and Hadith - Nuraini, Nabilah; taryudi (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2019)
The study of Qur'anic verses in the classification of qath'iy and zhanniy is known to be not a new discourse. Muslim scientists in the classical era have initiated the discussion of qath'iy and zhanniy within the framework of ijtihad in understanding texts in the contemporary era, the issue of qath'iy and zhanniy, even though their discussion has been preceded in the classical era, it is realized that they still leave room for discussion related to their contextualism rather than simply its dogmative doctrine. From the perspective of scientific authority, for example, there is a view that suggests that the issue of qath'iy and zhanniy is more appropriate to be a discourse on ushul fiqh rather than 'ulum Al-QurÄn and was not one of the subjects of discussion for muftassirin in the process of interpretation. Other than that, According to Imam As-Syatibi, the categorization of Qur'anic verses into qathiy and zhanniy is the ulama's ijtihad which does not have to be viewed dogmatically. So that in terms and applications qathiy and zhanniy must be understood in a more dynamic sense.